2012
DOI: 10.1136/annrheumdis-2011-200348
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept modulates proinflammatory macrophage responses upon cytokine-activated T cell and Toll-like receptor ligand stimulation

Abstract: Tck induce the production of TNFa by macrophages and facilitate the highly increased production of proinflammatory cytokines in the presence of TLR ligands. Abatacept was shown to potently suppress these pathways suggesting that its role may extend beyond antigen specific T cell mediated effector function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…These data suggest that abatacept might exert alternate modes of action independent from T-cell activation blockade, as it was described in collagen-induced arthritis 26. This might also be consistent with additional effects of abatacept observed on others cell types expressing CD80/CD86 on their surfaces, including B cells27 28 and monocytes 29 30. However, we observed that abatacept failed to protect CB17-SCID mice from the development of bleomycin-induced dermal fibrosis, which strongly supports that T cells directly drive the antifibrotic properties of abatacept in this model.…”
Section: Discussionsupporting
confidence: 82%
“…These data suggest that abatacept might exert alternate modes of action independent from T-cell activation blockade, as it was described in collagen-induced arthritis 26. This might also be consistent with additional effects of abatacept observed on others cell types expressing CD80/CD86 on their surfaces, including B cells27 28 and monocytes 29 30. However, we observed that abatacept failed to protect CB17-SCID mice from the development of bleomycin-induced dermal fibrosis, which strongly supports that T cells directly drive the antifibrotic properties of abatacept in this model.…”
Section: Discussionsupporting
confidence: 82%
“…CD4 +  cells were isolated from HCs (n = 6) using CD4 microbeads (Militenyi) and the memory T cell subpopulation expanded and activated by incubation with IL-15 (25 ng/ml), TNF (25 ng/ml) and IL-6 (100 ng/ml) as described before [8]. CD14 +  cells from the same donors were differentiated to macrophages by incubation with M-CSF (50 ng/ml).…”
Section: Methodsmentioning
confidence: 99%
“…CD14 +  cells from the same donors were differentiated to macrophages by incubation with M-CSF (50 ng/ml). After 6 days T cells were added to monocyte-derived macrophages at a ratio of 8:1 for 24 h as described, and in situ hybridization for miR-155 in macrophages was performed [8]. …”
Section: Methodsmentioning
confidence: 99%
“…Abatacept also favorably reduces intercations between T cells, dendritic cells and macrophages to reduce down stream cytokine release [33,34] and may inhibit osteoclastogenesis [33,34]. Murine models show that at least some of the beneficial effects of abatacept are mediated via reduction of reverse licencing of dendritic cells by T cells though such data are currently being investigated in human trials [35].…”
Section: T Cells In Ramentioning
confidence: 99%